2021
DOI: 10.3390/land10030277
|View full text |Cite
|
Sign up to set email alerts
|

Strategies of Landscape Planning in Peri-Urban Rural Tourism: A Comparison between Two Villages in China

Abstract: Landscapes have multiple functions relating to natural preservation and cultural inheritance, which are fundamental factors for tourist development. Particularly in villages, rural tourism is primarily based on the rural landscape. However, peri-urban villages face complex conflicts of urbanization and ruralism, in which landscapes are dynamic and need synergistic plans and management. Thus, this research contributes to a better understanding of comprehensive landscape planning integrating natural and cultural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…Preliminary screening of indicators: Analyze and sort out relevant evaluation indicators for village economic production [19][20][21][22][23], human settlement environment [15,[24][25][26][27], village ecological and cultural value [28][29][30], diversity of traditional village [31][32][33][34], policy efficiency index [35,36], and adaptability of rural tourism [17,32,[37][38][39] from available literature. Finally, a total of 52 evaluation indicators were selected according to the objectives and principles mentioned above.…”
Section: Index Screening and Expert Consultationmentioning
confidence: 99%
“…Preliminary screening of indicators: Analyze and sort out relevant evaluation indicators for village economic production [19][20][21][22][23], human settlement environment [15,[24][25][26][27], village ecological and cultural value [28][29][30], diversity of traditional village [31][32][33][34], policy efficiency index [35,36], and adaptability of rural tourism [17,32,[37][38][39] from available literature. Finally, a total of 52 evaluation indicators were selected according to the objectives and principles mentioned above.…”
Section: Index Screening and Expert Consultationmentioning
confidence: 99%
“…The development of SMCs is primarily influenced by their place in the regional transportation plan (e.g., highways) [ 20 , 21 ]. Some small village-like cities are facing a shortage of sanitation facilities [ 22 ]. Although SMCs are facing competition from big cities, especially in population attractiveness [ 19 , 23 ], a previous study has revealed that the key attractive factors in big cities, such as diversity, density, and entertainment, have a much weaker effect in SMCs [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…In response to the call of rural revitalization strategy, many researchers have put forward the concept of village construction based on a dynamic programming algorithm [1]. Facing the ownership of village residents, the corresponding planning should follow the villagers' own wishes for improvement [2]. e completion of village planning is the basis and guarantee for the construction and management of rural areas and is conducive to promoting the construction of a new socialist countryside [3].…”
Section: Introductionmentioning
confidence: 99%